Integrating Medical Acupuncture and Intraoral Dry Needling Protocol for Radiation-Induced Xerostomia - S. J. Lee; C. P. Diep; S. Arman; D. V. Messadi; F. S. Younai (Journal of the California Dental Association)
Clinical trials have shown that acupuncture may be effective in treating xerostomia.2 Acupuncture reduces symptoms related to xerostomia in patients who are refractory to current management such as pilocarpine.3 A 60-year old female patient presented with xerostomia after receiving radiation for adenoid cystic carcinoma. Patient reported attempting various treatment modalities to improve RIX that included but not limited to Pilocarpine prescription and over the counter saliva substitutes. After 3 months, patient decided to seek care at UCLA School of Dental Medicine’s Orofacial Pain Clinic for dental acupuncture treatment. We opted to utilize Dr Niemtzow’s protocol for this case study. Dr Richard Niemtzow, a colonel in the US Air Force, created an acupuncture protocol that is point precise to treat radiotherapy-induced xerostomia (RIX) for cancer patients.6 Per Dr Niemtzow’s medical acupuncture protocol, three auricular and four digital points were bilaterally placed for 45 minutes. Patient subsequently received intraoral dry needling protocol on two tongue and two palatal acupuncture points for two minutes. Treatment was repeated the next day. By including dental acupuncture after Dr Niemtzow’s protocol, saliva production increased by an average of two times more compared to Dr Niemtzow’s stand alone treatment. The intraoral acupuncture protocol may have additionally stimulated the parotid, submandibular, sublingual, and minor palatal salivary glands, resulting in an increase of salivary production. Studies have shown at least two neuropeptides, vasoactive intestinal peptide and calcitonin gene-related peptide, to be present in salivary glands that can stimulate salivary secretion.7 The intraoral dry needling protocol is an invaluable addition to provide relief from radiation-induced xerostomia. Further investigation with a larger patient population should be considered to standardize dental acupuncture.